PROFESIONALISME GURU DALAM MENINGKATKAN MUTU PENDIDIKAN - Nurlaila Nurlaila (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
The increasing of educational quality is geared towards educators (teachers and lecturers) quality. The availability of substantial funds, complete infrastructure, as well as various other educational components will not ensure the achievement of the goal of increasing the quality of education, if the quality of the teachers is not improved as well.Quality improvement can be done by a professional teacher. In addition, the teacher must be a professional educator with who can teach students by heart, explore, discover unique talents of learners, train the students, guide their life, and lead them to the way to know their Almighty Allah Swt., so that later participants will become useful person for other generations, for their era, the world and be proud to return to his Lord.